The Role of Soluble Urokinase Plasminogen Activator Receptor (suPAR) in the Context of Aneurysmal Subarachnoid Hemorrhage (aSAH)—A Prospective Observational Study - Schmidt, Tobias P.; Albanna, Walid; Weiss, Miriam; Veldeman, Michael; Conzen, Catharina; Nikoubashman, Omid; Blume, Christian; Kluger, Daniel S.; Clusmann, Hans; Loosen, Sven H.; Schubert, Gerrit A. (Frontiers in Neurology, 2022)
Objective Outcome after aneurysmal subarachnoid hemorrhage (aSAH) is highly variable and largely determined by early brain injury and delayed cerebral ischemia (DCI). Soluble urokinase plasminogen activator receptor (suPAR) represents a promising inflammatory marker which has previously been associated with outcome in traumatic brain injury and stroke patients. However, its relevance in the context of inflammatory changes after aSAH is unclear. Here, we aimed to characterize the role of circulating suPAR in both serum and cerebrospinal fluid (CSF) as a novel biomarker for aSAH patients. Methods A total of 36 aSAH patients, 10 control patients with unruptured abdominal aneurysm and 32 healthy volunteers were included for analysis. suPAR was analyzed on the day of admission in all patients. In aSAH patients, suPAR was also determined on the day of DCI and the respective time frame in asymptomatic patients. One- and two-sample t-tests were used for simple difference comparisons within and between groups. Regression analysis was used to assess the influence of suPAR levels on outcome in terms of modified Rankin score. Results Significantly elevated suPAR serum levels (suPAR-SL) on admission were found for aSAH patients compared to healthy controls, but not compared to vascular control patients. Disease severity as documented according to Hunt and Hess grade and modified Fisher grade was associated with higher suPAR CSF levels (suPAR-CSFL). In aSAH patients, suPAR-SL increased daily by 4%, while suPAR-CSFL showed a significantly faster daily increase by an average of 22.5 % per day. Each increase of the suPAR-SL by one ng/ml more than tripled the odds of developing DCI (OR = 3.06). While admission suPAR-CSFL was not predictive of DCI, we observed a significant correlation with modified Rankin’s degree of disability at discharge. Conclusion Elevated suPAR serum level on admission as a biomarker for early inflammation after aSAH is associated with an increased risk of DCI. Elevated suPAR-CSFL levels correlate with a higher degree of disability at discharge. These distinct relations and the observation of a continuous increase over time affirm the role of inflammation in aSAH and require further study.